The association between binge drinking and birth outcomes: results from the Born in Bradford cohort study. Issue 10 (31st May 2013) - Cooper, Duncan L; Petherick, Emily S; Wright, John
Abstract : Background: Various human and animal studies suggest that peak alcohol exposure during a binge episode, rather than total alcohol exposure, may determine fetal development. Research about the impact of binge drinking on birth outcomes is sparse and inconclusive. Data from the Born in Bradford cohort study were used to explore the impact of binge drinking on birth outcomes. Methods: Interview-administered questionnaire data about the lifestyle and social characteristics of 10 851 pregnancies were linked to maternity and birth data. The impact of self-reported binge drinking (5 units: 40 g of pure alcohol) on two birth outcomes (small for gestational age (SGA) and preterm birth (<37 weeks)) was assessed using multivariate logistic regression models, while adjusting for confounders. Results: The percentage of women classified as binge drinkers fell from 24.5% before pregnancy to 9% during the first trimester and 3.1% during the second trimester. There was a significant association between SGA birth and binge drinking (all categories combined; OR 1.68, 95% CI 1.15 to 2.47, p=0.01). No association was observed between moderate drinking and either birth outcome, or between binge drinking and preterm birth. Conclusions: Binge drinking during the second trimester of pregnancy was associated with an increased risk of SGA birth. No association was found between any level of alcohol consumption and premature birth. This work supports previous research showing no association between SGA and low-alcohol exposure but adds to evidence of a dose–response relationship with significant risks observed at binge drinking levels.